2022
DOI: 10.1007/s11663-022-02605-3
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Behaviour in Ferroalloys: The Influence of FeMn Slag Composition

Abstract: The present study investigated the interfacial interaction between FeMn alloy and slags of different compositions and basicity from 0.4 to 1.2 in a sessile drop furnace. Interfacial tension between the FeMn alloy and the slags was measured, and the results were analyzed to assess the sensitivity of the applied methodology. The measurement of the interfacial tension was based on combining the results from experiments, multiphase flow simulations in OpenFOAM, equilibrium calculations in FactSage, and calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In addition, because Marangoni flow is a function of viscosity, it is proposed that the emulsion of metal in slag decreases with increased viscosity. This was found for a similar metal-slag system [26]. For the present system, it can be qualitatively observed in the work of Solbakk [20] for less viscous CaO-SiO2 slag with a decreasing CaO/SiO2 ratio.…”
Section: Hydrodynamic Phenomenasupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, because Marangoni flow is a function of viscosity, it is proposed that the emulsion of metal in slag decreases with increased viscosity. This was found for a similar metal-slag system [26]. For the present system, it can be qualitatively observed in the work of Solbakk [20] for less viscous CaO-SiO2 slag with a decreasing CaO/SiO2 ratio.…”
Section: Hydrodynamic Phenomenasupporting
confidence: 87%
“…Extensive research on the interaction between liquid high-Al steel and liquid CaO-SiO 2 -Al 2 O 3 slag has consistently demonstrated that the metallothermic reaction described by Equation ( 2) drives interfacial phenomena [20,[23][24][25][26][27][28]. Observations and explanations of these interfacial phenomena are well documented, encompassing various metal-slag systems, such as Fe-Mn in contact with CaO-SiO 2 -MnO [26] and Cu-Ni-Al alloy with Li 2 O-Al 2 O 3 -SiO 2 [29]. However, the relative significance of these phenomena in influencing overall reaction kinetics remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, slag is formed in many processes [99][100][101][102][103][104][105][106][107]; for example, ironmaking, convertor steelmaking, refining, continuous casting, the electroslag remelting process, and ferroalloys production. The thermodynamic properties and physicochemical properties of many types of slags have been widely evaluated and modeled [108][109][110][111][112][113][114].…”
Section: Introductionmentioning
confidence: 99%
“…Ген PRLR детерминирует рецептор гормона передней доли гипофиза -пролактина, который в организме млекопитающих участвует в регуляции роста, метаболизма и размножения [33]. Ген рецепторов проталактина (PRLR) -один из самых универсальных гормонов гипофиза, он является потенциальным генетическим маркером признаков молочной продуктивности в животноводстве.…”
Section: введение / Introductionunclassified